OPTIMALISASI PENGGUNAAN E-MODUL DAN PHET SIMULATION SEBAGAI VIRTUAL LAB DI MASA PANDEMI COVID-19 - Vepy Asyana; Arini Arini (Komunikasi Fisika Indonesia, 2020)
This study examines the use of e-modules and PhET simulations as virtual labs in basic physics. The purpose of this research is to optimize the available virtual labs. To facilitate the implementation of practicum, this study uses e-module as a companion material used by users. The research was conducted in two stages. The first is conducting direct trials using PhET simulations and e-modules through Google classroom. The second stage is primary data collection through a questionnaire instrument given to respondents via Google form. The questionnaire instrument was then analyzed by testing the validity, reliability and usability. From the validity and reliability test results obtained 9 question items that have valid and reliable criteria of 0.936 with very high criteria. The usability results show the percentage of respondents to the questions given through the questionnaire dominated by agreeing and strongly agreeing to the four usability factors. This shows that the use of e-module and PhET simulation as virtual lab fulfills the usability element.